2023
DOI: 10.21203/rs.3.rs-2776581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell profiling of mosquito spermatogenesis defines the onset of meiotic silencing and pre-meiotic overexpression of the X chromosome.

Abstract: Understanding of the Anopheles gambiae germline has been essential to acquiring effective genetic control strategies targeting this malaria mosquito vector. This includes targeting germline genes to induce sterility or using regulatory sequences to drive transgene expression for applications such as gene drive. However, only very few germline regulatory elements have been characterised with the majority showing leaky expression. This has been shown to significantly reduce the efficiency of current genetic cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…We observed that expression of Xchromosome genes is already extremely depressed in GSC and rises in expression until secondary spermatocytes. The main difference with other species here is the scale, as we only observed an X-Autosome expression ratio of 0.2% while other insect species note minima never crossing below 20% Page et al, 2023). This implies an overall suppression of the X chromosome and MSCI more absolute than other species and localized entirely to meiotic cells unlike what has been observed in Drosophila (Mikhaylova & Nurminsky, 2011;Meiklejohn et al, 2011;Vibranovski et al, 2012;Landeen et al, 2016;Witt et al, 2021;Mahadevaraju et al, 2021;Prince et al, 2010).…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…We observed that expression of Xchromosome genes is already extremely depressed in GSC and rises in expression until secondary spermatocytes. The main difference with other species here is the scale, as we only observed an X-Autosome expression ratio of 0.2% while other insect species note minima never crossing below 20% Page et al, 2023). This implies an overall suppression of the X chromosome and MSCI more absolute than other species and localized entirely to meiotic cells unlike what has been observed in Drosophila (Mikhaylova & Nurminsky, 2011;Meiklejohn et al, 2011;Vibranovski et al, 2012;Landeen et al, 2016;Witt et al, 2021;Mahadevaraju et al, 2021;Prince et al, 2010).…”
Section: Discussioncontrasting
confidence: 87%
“…This atlas gives us the ability to directly compare to other studies in Drosophila and mosquito Page et al, 2023). We did not observe separate clusters for germline and cyst cells, likely due to a lack of known beetle markers for cyst cells for the weighted principal components, however the mosquito study also did not identify separate clusters for cyst cells.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations